Chronic exposure to di‐n‐butyl phthalate causes reproductive toxicity in zebrafish. Issue 12 (5th July 2020) - Hu, Jianxin; Jiang, Kehua; Tang, Xiaohu; Liu, Hao; Zhang, Hu; Yang, Xuefeng; Nie, Xiangqian; Luo, Heng
Abstract: Di‐n‐butyl phthalate (DBP) is known to have adverse effects on reproduction in mammals and is pervasive in the aquatic environment. The objective of the present study was to investigate whether long‐term exposure to low concentrations of DBP can affect fish reproduction. In this study, zebrafish ( Danio rerio ) embryos (F0 ) were exposed to low concentrations (4.9, 13.6 and 43.8 μg/L) of DBP from 2 hours post‐fertilization until sexual maturation. The results demonstrate that chronic exposure to DBP (43.8 μg/L) impaired the reproductive function of zebrafish, as verified by reduced egg production and modifications to gonadal histology of the treated fish. Plasma 17β‐estradiol levels in female zebrafish decreased significantly in a concentration‐dependent manner, while testosterone levels in males increased significantly when fish were exposed to 43.8 μg/L DBP. Real‐time polymerase chain reaction was performed to examine selected genes in the hypothalamic‐pituitary‐gonadal (HPG) axis and liver. Hepatic vitellogenin gene transcription was downregulated in both males and females, suggesting that DBP possesses anti‐estrogenic activity. The disturbed steroid hormones were accompanied by the significant alterations in gene expression along the HPG axis. Additionally, parental exposure to DBP caused reduced hatching and survival rate as well as decreased growth in the F1 generation. Taken together, these results demonstrate that long‐term exposure to low concentrations of DBP in zebrafish could cause reproductive toxicity, implying that DBP could have significant adverse effects on fish populations, particularly in a highly DBP‐contaminated aquatic environment. Abstract : Di‐n‐butyl phthalate (DBP) is known to have adverse effects on reproduction in mammals and is pervasive in the aquatic environment. The objective of the present study was to investigate whether long‐term exposure to low concentrations of DBP can affect fish reproduction. In this study, zebrafish ( Danio rerio ) embryos (F0 ) were exposed to low concentrations (4.9, 13.6 and 43.8 μg/L) of DBP from 2 hours post‐fertilization until sexual maturation.